XV. studentská vědecká konference Katedry českého jazyka a literatury 23. března 2023 - Zuzaňáková, Kristýna (Sborník prací Pedagogické fakulty Masarykovy univerzity, 2023)
Title in English: The XVth Student Academic Conference of the Department of Czech Language and Literature: 23th March 2023 These collection of the XV. student scientific conference of the Department of Czech Language and literature from March 23, 2023, contains 15 articles by 15 researchers on linguistic and literary topics. It contains studies by Kristýna Zuzaňáková (The metaphors of everyday life), Iveta Dokoupilová (Carrying children in linguistics), Tereza Švandová (Czech Language as the basis of success or the Role of Czech for foreign language speakers), Radim Ošmera (Interlanguage theory in second language acquisition), Zuzana Procházková (Textbooks for pupils with different mother tongue at the second level of primary school), Aneta Čermáková (Strengths and limitations of corpus analysis of bilingual material), Petra Fojtíková (Literacy and literacy in literary education classes), Miroslav Jindra (Conclusion to the research on children's identification with literary works and theatre performances), Marie Pavelková (The figure of the child-stranger in Alena Ježková's Dragon soup), Magdalena Lípová (The dog hero as a guide on the way to identity formation and interpersonal relationships in selected stories for children and youth), Klára Březinová (Marian mirroring), Dominika Papíková (Internal subjects in Petra Soukupová's books To the sea and The best for all), Ondřej Zabloudil Pechník (The thematization of natural nations in Czech literature after 2000 in retrospect), Tereza Homolová (The theme of music in the poetry of Vít Slíva) and Tereza Pořízková (Above aspects of the novel by E. M. Forster).